PENGARUH PENGUNGKAPAN (DISCLOSURE) TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar Di Bursa Efek Indonesia Tahun 2013-2014) - Rahmi Surya Ningsih; Zulbahridar '; Hariadi Yasni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was aimed to investigate the effects of disclosure to earnings management in consumer goods industry sector companies listed in Indonesian Stock Exchange. The data of this research was the data secondary based on the report of finances and the report of the year companies. The population of this research were consumer goods industry sector manufacturing companies listed in Indonesia Stock Exchange in 2013-2014. In this research, the sampling was done by using purpose sampling method. From 39 consumer goods industry sector companies, 29 companies were selected according to criteria of research sample. The data analysis tool used in this research was simple regression. The results of this study show that size of disclosure effect on earnings management to the value thitung (-4,953) < ttable (-2,003) on the level significant is (α) < 0,05. Thus, the greater of the level disclosure that is disclosed by the company the less likely the occurence of earnings management practices, and vice versa. Determination coefficient in this research is 0,305 means inflicted (R2) by the independent variable in explaining the dependent variable was 30.5%, while the remaining 69.5% was influenced by other variables which were not included in this research.Keyword : disclosure and earnings management.